Evaluation of Salaries and Their External Factors in the Baltic Countries - Liaudanskienė, Ieva (Buhalterinės apskaitos teorija ir praktika, 2025)
Wages remain one of the most relevant factors from both microeconomic and macroeconomic perspectives. The aim of this study is to assess the impact of external factors on the average wage in the Baltic countries, as well as across different sectors of economic activity. The study covers the period from 2011 to 2023, incorporating significant macroeconomic shifts such as the COVID-19 pandemic and the war in Ukraine. The novelty of the research lies in its cross-country (Lithuania, Latvia, Estonia) and sectoral analysis. The research includes an expert survey, dynamic analysis of selected indicators, and applies correlation and regression analysis methods. These methods enable the evaluation of how external factors—such as GDP, minimum monthly wage (MMW), unemployment, foreign direct investment (FDI), inflation, the number of employed individuals with higher education, and tax policy—affect average wages in individual Baltic countries, the Baltic region as a whole, and various sectors of economic activity (classified according to NACE). The results indicate that average wages in Lithuania are influenced by inflation, MMW, and employment; in Latvia—by FDI and employment; and in Estonia—by GDP and inflation. For the Baltic region as a group, the average wage is primarily affected by MMW and GDP. Sectoral analysis reveals that these factors have varying impacts across countries and sectors.
Keywords: average wage; external factors; Baltic countries; labor market; economic analysis